Insights about the epidemiology of Salmonella Typhimurium isolates from different sources in Brazil using comparative genomics - Seribelli, Amanda Ap.; da Silva, Patrick [UNESP]; da Cruz, Marcelo Ferreira; de Almeida, Fernanda; Frazão, Miliane R.; Medeiros, Marta I. C.; Rodrigues, Dália dos P.; Kich, Jalusa D.; de Jesus Benevides, Leandro; Soares, Siomar de C.; Allard, Marc W.; Falcão, Juliana Pfrimer. (Springer Nature, 2021)
Background: Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) is an important zoonotic agent worldwide. The aim of this work was to compare genetically 117 S. Typhimurium isolated from different sources over 30 years in Brazil using different genomics strategies. Results: The majority of the 117 S. Typhimurium strains studied were grouped into a single cluster (≅ 90%) by the core genome multilocus sequence typing and (≅ 77%) by single copy marker genes. The phylogenetic analysis based on single nucleotide polymorphism (SNP) grouped most strains from humans into a single cluster (≅ 93%), while the strains isolated from food and swine were alocated into three clusters. The different orthologous protein clusters found for some S. Typhimurium isolated from humans and food are involved in metabolic and regulatory processes. For 26 isolates from swine the sequence types (ST) 19 and ST1921 were the most prevalent ones, and the ST14, ST64, ST516 and ST639 were also detected. Previous results typed the 91 S. Typhimurium isolates from humans and foods as ST19, ST313, ST1921, ST3343 and ST1649. The main prophages detected were: Gifsy-2 in 79 (67.5%) and Gifsy-1 in 63 (54%) strains. All of the S. Typhimurium isolates contained the acrA, acrB, macA, macB, mdtK, emrA, emrB, emrR and tolC efflux pump genes. Conclusions: The phylogenetic trees grouped the majority of the S. Typhimurium isolates from humans into a single cluster suggesting that there is one prevalent subtype in Brazil. Regarding strains isolated from food and swine, the SNPs’ results suggested the circulation of more than one subtype over 30 years in this country. The orthologous protein clusters analysis revealed unique genes in the strains studied mainly related to bacterial metabolism. S. Typhimurium strains from swine showed greater diversity of STs and prophages in comparison to strains isolated from humans and foods. The pathogenic potential of S. Typhimurium strains was corroborated by the presence of exclusive prophages of this serovar involved in its virulence. The high number of resistance genes related to efflux pumps is worrying and may lead to therapeutic failures when clinical treatment is needed.
Keywords: Efflux pumps; Phylogenetic trees; Prophages; Protein orthologous clusters; Salmonella Typhimurium